PENGARUH PELAYANAN, CITRA MEREK DAN HARGA TERHADAP PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN DAN WORD OF MOUTH - Rambe, Neni; Maksum, Choirul; Yasin, Moch (SEKOLAH PASCASARJANA PRESS, 2017)
The aim of this research explain the relationship and the influence of several variables that have been defined. Data analysis techniques using Structural Equation Model (SEM). Distributing questionnaires conducted with purposive sampling method. A population of 725 respondents with a defined sample 120 respondents. The result of the analysis of this data showed that, service quality variables positive and significantly influence repurchase, the customer satisfaction and word of mouth, variable brand image positive and significantly influence repurchase, the customer satisfaction and word of mouth, variable price positive and significantly influence repurchase, the customer satisfaction and word of mouth, variable customer satisfaction positive and significantly influence repurchase and word of mouth, variable word of mouth positive and significantly influence repurchase.